(untitled) (Journal of the Medical College for Women & Hospital, 2026)
BACKGROUND: Subfertility, a growing global issue, arises from diverse gynecological factors including pelvic pathologies. While laparoscopy is the diagnostic gold standard, it is invasive and costly. Transvaginal ultrasonography (TVS) offers a less invasive, affordable alternative, yet its diagnostic accuracy for pelvic pathology in subfertile women requires validation.Aim:To assess and compare the detection of gross pelvic pathology in subfertile women by TVS and laparoscopy.Materials and Method:This cross-sectional study enrolled 100 subfertile women aged 20–40 years at Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) General Hospital, Dhaka, from January to December 2015. All underwent TVS followed by diagnostic laparoscopy. Data collection included clinical examination, sonography, and surgical findings.Results: The study included women aged 20–40 years, predominantly between 26 and 35 years. Among them, 61% had primary and 39% had secondary subfertility. TVS identified a normal uterus in 66% and fibroids in 14% of cases, comparable to laparoscopy findings (76% normal uterus, 14% fibroids). TVS detected normal ovaries in 56% and polycystic changes in 32%, while laparoscopy detected 40% and 38%, respectively. Fallopian tubes were visualized in 96% by TVS and 84% by laparoscopy. However, TVS failed to detect peritubular adhesions visible in 14% by laparoscopy. Hydrosalpinx was observed in 4% by TVS and 2% by laparoscopy. Pouch of Douglas abnormalities and endometriosis were underdiagnosed by TVS compared to laparoscopy. Overall, TVS demonstrated a sensitivity of 62.87%, specificity of 81%, positive predictive value of 89%, and negative predictive value of 49% in detecting pelvic pathology.Conclusion:TVS is a valuable, noninvasive tool for detecting uterine and some ovarian pathologies in sub-fertile women. Yet, it has limitations in detecting tubal and peritoneal disease, emphasizing that laparoscopy remains necessary for definitive diagnosis in complex cases. J Med Coll Women Hosp.2026; 22(1): 42-52